Network Pharmacology-Based Analysis of Xiao-Xu-Ming Decoction on the Treatment of Alzheimer’s Disease - Shen, Yanjia; Zhang, Baoyue; Pang, Xiaocong; Yang, Ran; Chen, Miao; Zhao, Jiaying; Wang, Jinhua; Wang, Zhe; Yu, Ziru; Wang, Yuehua; Li, Li; Liu, Ailin; et al. (Frontiers in Pharmacology, 2020)
Alzheimer's disease (AD) has become a worldwide disease that is harmful to human health and brings a heavy economic burden to healthcare system. Xiao-Xu-Ming Decoction (XXMD) has been widely applied to treat stroke and other neurological diseases for more than 1000 years in China. However, the synergistic mechanism of the constituents in XXMD for the potential treatment of AD still remains unclear. Therefore, the present study aimed to predict the potential targets and uncover the material basis of XXMD for the treatment of AD. A network pharmacology-based method, which combined data collection, drug-likeness filtering and ADME/T properties filtering, target prediction and network analysis, was used to decipher the effect and potential targets of XXMD for the treatment of AD. Then, the in vitro AChE inhibitory assay was used to screen the potential active constituents in XXMD for the treatment of AD, and the molecular docking was used to identify the binding ability of active constituents with AD-related targets. Finally, three in vitro cell models were applied to evaluate the neuroprotective effects of fangchinoline. Through the China Natural Products Database, TCMSP Database, TCM-Database @Taiwan and literature, a total of 1481 ingredients were finally collected. After ADME/T properties filtering, 908 ingredients were kept for the further study. Based on the prediction data, the constituents in XXMD formula could interact with 41AD-related targets, and cyclooxygenase-2 (COX-2), estrogen receptor α (ER) and acetylcholinesterase (AChE) were the major targets. The constituents in XXMD were found to treat AD through multiple AD-related targets and 62 constituents interacted with more than or equal to 10 targets. The prediction results were further validated by in vitro experiment, resulting in several potential anti-AD multitarget-directed ligands (MTDLs), including two acetylcholinesterase (AChE) inhibitors with the IC50 values ranging from 4.83 to 10.22 μM. Between them, fanchinoline was further confirmed to prevent SH-SY5Y cells from the cytotoxicity induced by sodium nitroprusside, sodium dithionate and potassium chloride. XXMD was found to have the potential to treat AD by targeting multiple targets and canonical pathways. Fangchinoline and dauricine might be the potential lead constituents in XXMD for the treatment of AD.